Easy to remember, difficult to forget: The development of fear regulation. (February 2015) - Johnson, D.C.; Casey, B.J.
Highlights: Adolescent humans and rodents show diminished cued-fear extinction. Early-life stress in humans and rodents persistently alters fear regulation. BDNF Val66Met genotype diminishes cued-fear extinction learning. Age and BDNF genotype may impact the efficacy of exposure-based therapies. Abstract: Fear extinction learning is a highly adaptive process that involves the integrity of frontolimbic circuitry. Its disruption has been associated with emotional dysregulation in stress and anxiety disorders. In this article we consider how age, genetics and experiences shape our capacity to regulate fear in cross-species studies. Evidence for adolescent-specific diminished fear extinction learning is presented in the context of immature frontolimbic circuitry. We also present evidence for less neural plasticity in fear regulation as a function of early-life stress and by genotype, focusing on the common brain derived neurotrophin factor (BDNF) Val66Met polymorphism. Finally, we discuss this work in the context of exposure-based behavioral therapies for the treatment of anxiety and stress disorders that are based on principles of fear extinction. We conclude by speculating on how such therapies may be optimized for the individual based on the patient's age, genetic profile and personal history to move from standard treatment of care to personalized and precision medicine.